Microbiological Profile and Drug Sensitivity Pattern in Persistently Discharging Ears: A Tertiary Level Hospital Based Retrospective Study - Gyawali, Bigyan R; Pradhanaga, Rabindra B; Rayamjhi, Pabina; Dongol, Kripa; Gupta, Mudit; Shrestha, Lava; Acharya, Kunjan (Journal of Institute of Medicine Nepal, 2020)
Introduction Antimicrobial resistance is an emerging issue resulting from the misuse of antibiotics in today’s world. As an effect of it, cases with persistent ear discharge not responding to the conventional oral antibiotics prescribed in ear pathologies are seen increasing in our day to-day practice. This study aims to review the microbiological growth and the pattern of their antibiotic sensitivity in this group of population.MethodsThis was a retrospective study which was conducted at the Department of ENT-HNS of Tribhuvan University Teaching Hospital. Record files of all cases who presented with persistently discharging ear for more than 2 weeks and not responding to oral antibiotics, between January 2017 to March 2020 were assessed. Cases of chronic otitis media (COM) squamous with persistent discharge were excluded as most of the times it is the disease process rather than type of organism which causes the persistence of ear discharge despite the use of antibiotics.ResultsCOM mucosal and cavity infection following modified radical mastoidectomy (MRM) were the commonest pathologies. Pseudomonas aeruginosa (PA) and Coagulase negative Staphylococcus (CoNS) were the commonest bacterial isolates. Pseudomonas aeruginosa showed a good sensitivity to antibiotics like Tazobactam and Piperacillin and resistance to conventionally used antibiotics like Ciprofloxacin and Levofloxacin. Similarly, CoNS had good sensitivity to antibiotics like Oxacillin and Levofloxacin and resistance to conventionally used antibiotics like Amoxicillin.ConclusionCOM mucosal and post MRM cavity infection are the commonest pathologies presenting with persistent ear discharge with PA and CoNS as the predominant isolates. Pseudomonas aeruginosa holds a good sensitivity to drugs like Tazobactam and Piperacillin; and CoNS to drugs like Oxacillin and Levofloxacin.